Influence of Gadolinium-Based Contrast Agents on Tissue Sodium Quantification in Sodium Magnetic Resonance Imaging. Issue 9 (September 2018) - Paschke, Nadia Karina; Neumann, Wiebke; Uhrig, Tanja; Winkler, Manuel; Neumaier-Probst, Eva; Fatar, Marc; Schad, Lothar Rudi; Zöllner, Frank Gerrit
Abstract : Objectives: Sodium magnetic resonance (MR) imaging provides noninvasive insights to cellular processes by measuring tissue sodium concentration (TSC). Many clinical studies combine sodium MR imaging with clinical standard MR procedures, in which contrast media is frequently administered. This work investigates the influence of gadolinium-based contrast agents on quantification of TSC. Thus, either scan pauses between early and late contrast-enhanced acquisitions can be used efficiently or sodium imaging can be performed as the final scan after dynamic contrast-enhanced acquisition. Materials and Methods: For this study, 2 gadolinium-based contrast agents, Dotarem and Gadovist, were diluted with saline solution covering contrast agent concentrations in a clinical range. In addition, agarose-based sample series were created to simulate tissue relaxation time behavior. In vivo, the influence of Dotarem on sodium acquisition and TSC quantification was investigated in 1 ischemic stroke patient. Results: Proton relaxation times decreased for increasing contrast agent concentrations as hyperbolic functions. Sodium relaxation times displayed a negative slope in regression analysis in most cases. The largest influence (−1.52 milliseconds per mmol/L contrast agent) was measured for sodium T1 . Worst case calculations in ultrashort echo time sequence signal analysis showed a signal drop of (1.21% ± 0.56%) on tissue sodium quantification. In vivo sodium brain acquisitions of a stroke patient before and after Dotarem injection resulted in statistically nonsignificant differences in TSC quantification of relevant tissues and stroke areas ( P > 0.05). Conclusions: Our study showed a quantitative influence of Dotarem and Gadovist on sodium relaxation times. However, quantification of TSC was not impaired, which was proven by worst case calculations and nonsignificant differences in vivo in an ischemic stroke patient. We suggest performing sodium imaging in useful clinical positions in protocols regardless of included Dotarem or Gadovist administrations. Being flexible in the study protocol design will strengthen ongoing sodium imaging investigations for various pathologies.